Comparison of Quickness Item Test Results Based on Energy Source - Rahadiansyah, Muhammad Rizqi; Imanudin, Iman; Umaran, Unun; Subarjah, Herman (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objective. This study aimed to investigate how various energy sources impact individual reaction speed, formulate strategies for performance enhancement, and add to the body of scientific knowledge. This investigation examined the differences in quickness test outcomes according to various sequences of energy sources, emphasizing the impact of these sequences on quickness or reaction time among university students. Materials and methods. The investigation included 32 individuals from the Faculty of Sports Education and Health at Universitas Pendidikan Indonesia, class of 2022, comprising an equal number of male and female participants. The pretest-posttest experimental design involving a single group was employed, wherein the participants' speed was assessed through a straightforward test utilizing a falling ruler that needed to be caught with two fingers. A posttest was administered following the pretest, which featured the correct sequence of energy sources. The posttest utilized an incorrect order of energy sources to assess variations in performance. Data collection was conducted through purposive sampling, followed by analysis utilizing a paired t-test. Results. The findings indicated a notable reduction in quickness performance during the posttest. The statistical analysis indicated a significant reduction in the distance the ruler fell during the posttest when compared to the pretest (p < 0.05). A majority of participants demonstrated a reduction in reaction time, particularly among those with less favorable posttest outcomes. In summary, the arrangement of various energy sources notably influences performance in the quickness test. The results highlight the significance of adhering to established guidelines during training or testing, and offer valuable perspectives on how enhancing energy sources can elevate performance across different scenarios, particularly in athletic endeavors. Conclusion. The findings of this study indicate that varying sequences of energy sources significantly influence performance outcomes in the quickness test. The examination of the pretest and posttest outcomes revealed a distinct variation in participants' speed following the implementation of the energy source sequence. Suggestions for additional investigation involve examining a wider range of energy sources, utilizing varied subjects, taking psychological factors into account, and implementing long-term studies to gain a more profound understanding of the impact of energy sources on performance and health.